Transformation of Visionary and Collaborative Leadership Styles in Contributing Publication Innovation of Madrasah Aliyah - Alfaruqi, Alvi Fauzi; Fahmi, Nurkafidz Nizam (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This research aims to interpret the transformation of visionary and collaborative leadership styles in madrasah publication innovation. The object of this research is educational consumers MAN 2 Banyuwangi, This research design uses a qualitative approach with a case study method, The source of informants in this study consisted of the head of the madrasa, and teachers. MAN 2 Banyuwangi. Data collection in this study was carried out through in-depth interviews, direct observation, and publication documentation, Data analysis in this study uses an interactive analysis model developed by Miles, Huberman, which includes three main steps: data reduction, data presentation, and conclusion drawing. The results of this study indicate that the visionary and collaborative leadership styles at MAN 2 Banyuwangi are successful in contributing the publication innovation. The collaborative leadership strengthens educational community networks, transformation for resource management and innovation, to increasing Madrasah reputation.